IMPLEMENTASI KEBIJAKAN KAMPUNG TANGGUH SEMERU WANI JOGO SUROBOYO DI SURABAYA TIMUR - Fandy Putra Agustyawan; Mas Roro Lilik Ekowati; Lunariana Lubis (Faculty of Social and Political Science, 2021)
Kampung Tangguh Semeru is a program initiated by East Java Regional Police (POLDA) which is adapted in each area to reduce the spread of covid-19 pandemic in East Java. The program is known as Wani Jogo Suroboyo and written in the Mayor of Surabaya Regulation No. 67 Year 2020. The community has an active role in forming Kampung Wani in Rukun Warga and Rukun Tetangga areas. The study uses qualitative research method by applying case study approach in order to describe the implementation of Kampung Tangguh Semeru policy-Wani Jogo Suroboyo in East Surabaya. Furthermore, the purpose of the study identifies the inhibiting and supporting factors for the implementation of this policy that has four tasks, namely Wani Sehat, Wani Ngandani, Wani Jogo, and Wani Sejahtera. The result indicates the implementation of Kampung Tangguh Semeru-Wani Jogo Suroboyo is in accordance with the Regulation of the Mayor of Surabaya No. 67 Year 2020. It also points out the reduction on the number of covid-19 spread in Surabaya, especially in east districts. However, the funding sources are not implemented properly, which can be seen from the lack of financial assistance from the Surabaya government. In addition, the access of Lawan covid is closed for head of the task force in Rukun Warga area.